UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN DARING MELALUI MODEL PROBLEM BASED LEARING (PBL) TEMA 8 KELAS IV A SD NEGERI 2 PURWODADI TAHUN PELAJARAN 2020/2021 - Niken Hestining Servanda (Universitas Negeri Medan, 2021)
Abstract :The purpose of the study was to improve student learning outcomes in online learning through the Problem Based Learning (PBL) learning model theme 8 grade IV A SD Negeri 2 Purwodadi for the 2020/2021 school year. The initial data obtained that the quality of online learning in grade IV is not optimal, the teacher has not used problem-based learning so that students have not built their own knowledge through learning outcomes. Based on these problems the researchers determined solutions to improve the quality of learning through the Problem Based Learning (PBL) learning model. Problem Based Learning (PBL) is a teaching model that is characterized by real problems as a context for students to learn critical thinking and problem solving skills and gain knowledge. .The formulation of the problem in this study is how to improve teacher skills and student learning outcomes in learning theme 8 with the Problem Based Learning (PBL) model in class IV A SD Negeri 2 Purwodadi?. The purpose of the study was to improve teacher skills and student learning outcomes in learning theme 8 for class IV.This research uses classroom action research which consists of 3 cycles, each cycle has 1 meeting, and each cycle consists of 4 stages, namely planning, implementation, observation, and reflection. The research subjects were teachers and 15 students. Data collection techniques using test techniques. The data analysis technique used descriptive quantitative. The results showed that the teacher's skills in the first cycle got a score of 17 (good), the second cycle got a score of 19 (very good), and the third cycle got a score of 22 (very good). Classical completeness in the pre-cycle was 24.39%, the first cycle was 47%, the second cycle was 67% and the third cycle was 87%.The conclusion of this study is that the Problem Based Learning (PBL) model can improve the quality of learning theme 8 which includes teacher skills and learning outcomes. Suggestions: teachers should be able to make Problem Based Learning (PBL) models as an alternative to the learning process; students should be able to improve problem solving skills in real situations; and schools should facilitate teachers in improving the quality of learning. Keywords: Thematic, Learning Outcomes, Improvement, Online Learning, Problem Based Learning (PBL) Abstrak : Tujuan penelitian adalah untuk meningkatkan hasil belajar siswa dalam pembelajaran daring melalui model pembelajaran Problem Based Learning (PBL) tema 8 kelas IV A SD Negeri 2 Purwodadi tahun pelajaran 2020/2021. Data awal yang diperoleh kualitas pembelajaran daring di kelas IV belum optimal, guru belum menggunakan pembelajaran berbasis masalah sehingga siswa belum membangun pengetahuannya sendiri melalui hasil belajar. Berdasarkan permasalahan tersebut peneliti menetapkan solusi untuk meningkatkan kualitas pembelajaran melalui model pembelajaran Problem Based Learning (PBL).Problem Based Learning (PBL)adalah model pengajaran yang berciikan adanya permasalahan nyata sebagai konteks untuk para peserta didik belajar berpikir kritis dan keterampilan memecahkan masalah serta memperoleh pengetahuan. Rumusan masalah dalam penelitian ini adalah Bagaimanakah cara meningkatkan keterampilan guru dan hasil belajar siswa pada pembelajaran tema 8 dengan model Problem Based Learning (PBL) pada kelas IV A SD Negeri 2 Purwodadi?. Tujuan penelitian adalah meningkatkan keterampilan guru dan hasil belajar siswa pada pembelajaran tema 8 kelas IV. Penelitian menggunakan penelitian tindakan kelas yang terdiri dari 3 siklus, tiap siklus 1 pertemuan, dan tiap siklus terdiri atas 4 tahap, yaitu perencanaan, pelaksanaan, observasi dan refleksi. Subjek penelitian adalah guru dan 15 siswa. Teknik pengumpulan data menggunakan teknik tes. Teknik analisis data menggunakan deskriptif kuantitatif.Hasil penelitian menunjukkan keterampilan guru pada siklus I memperoleh skor 17 (baik), siklus II memperoleh skor 19 (sangat baik), dan siklus III memperoleh skor 22 (sangat baik). Ketuntasan klasikal pada prasiklus 24,39%, siklus I 47%, siklus II 67% dan siklus III 87%.Simpulan penelitian ini adalah model Problem Based Learning (PBL) dapat meningkatkan kualitas pembelajaran tema 8 yang meliputi keterampilan guru dan hasil belajar. Saran : guru hendaknya dapat menjadikan model Problem Based Learning (PBL) sebagai salah satu alternatif proses pembelajaran; siswa hendaknya dapat meningkatkan kemampuan memecahkan masalah dalam situasi nyata; dan sekolah hendaknya memfasilitasi guru dalam meningkatkan kualitas pembelajaran. Kata Kunci : Tematik; Hasil Belajar;Peningkatan;Pembelajaran Daring;Problem Based Learning(PBL)